Republic of Slovenia : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Slovenia. (IMF Staff Country Reports; Country Report, 2021)
The pandemic is inflicting much suffering, which has been met with swift, substantial, and well-coordinated policy responses. The anti-crisis measures have helped preserve jobs, provide liquidity to companies and income support to the vulnerable groups. They averted a larger decline in output and kept unemployment under control. After contracting by 5.5 percent in 2020, real GDP is projected to grow by 3.9 percent in 2021 and 4.5 percent in 2022, as vaccinations help achieve herd immunity. However, risks to the outlook are large and tilted to the downside, given the epidemiological situation.